THE NORTH OF EASTERN SIBERIA: REFUGE OF MAMMOTH FAUNA IN THE HOLOCENE - Boeskorov G.G. (My University, 2004)
The global climate changings at the end of Pleistocene led to extinction of the typical representatives of Mammoth fauna–mammoth, woolly rhinoceros, wild horse, bison, muskox, cave lion, etc.–on the huge territories of Northern Eurasia. Undoubtedly the Mammoth fauna underwent pressure from the Upper Paleolithic Man, whose hunting activity also could play the role in decreasing the number of mammoths and other representatives of megafauna (large mammals). Archaeological data testify that the typical representatives of Mammoth fauna were the Man's hunting objects only till the end of the Pleistocene. Their bone remains are not usually found on the settlements of Mesolithic Man. Formerly it was supposed that the megafauna of ‘Mammoth complex’ was extinct by the beginning of Holocene. Nevertheless the latest data testify that the global extinction of the Mammoth fauna was sufficiently delayed in the north of Eastern Siberia. In the 1990s some radiocarbon data testified that the mammoths on the Wrangel Island existed for a long time during the Holocene from 8000 till 3700 y. BP. The present radiocarbon data show that wild horses inhabited the north of Eastern Siberia (the lower stream of the Enissey river, the Novosibirskie Islands, the East Siberian sea-shore) 3000–2000 y. BP. Musk-oxen lived on the Taimyr Peninsula and the Lena River delta about 3000 y. BP. Some bison remains from Eastern Siberia belong to the Holocene. The following circumstances could promote the process of preservation of the Mammoth fauna representatives. The cool and dry climate of this region promotes the maintenance of steppe associations – habitats of those mammals. The Late Paleolithic and Mesolithic settlements are not found in the Arctic zone of Eastern Siberia from the Taimyr Peninsula to a lower stream of the Yana River; they are very rare in the basins of the Indigirka and Kolyma Rivers. So, the small number of the Stone Age hunting tribes on the North of Eastern Siberia was another factor in the long-term preservation of some Mammoth fauna representatives.
Keywords: Holocene; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен